FAKTOR FAKTOR YANG BERPENGARUH TERHADAP EFEKTIVITAS AUDIT INTERNAL (Studi Pada Inspektorat Provinsi Jawa Tengah) - Rheza Rahadhitya; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of auditor experience, risk management, education, training, effective internal control system, dan management support on internal audit effectiveness in Inspectorate of Cental Java.The population of this study are the auditors of Inspectorate of Central Java which totaling 33 peoples. Because the small number of the population, therefore in this study is using census method, which uses the population as a sample. The data for this study were obtained through a questionnaire administrated to the auditors in Inspektorat Provinsi Jawa Tengah. The data were analyzed using SPSS version 20, hence the hypotesis are tested by the multiple regression analysis.The result showed that auditor experience, education, training and effective internal control system has significant positive effect on internal audit effectiveness. Whereas risk management and management support has no significant effect on internal audit effectiveness.